Decolorization of Methylene Blue Dye Using ZnO/ZSM-5 Photocatalyst under UV-LED Irradiation - Lely Dwi Astuti; Yuly Kusumawati; Wahyu Bambang Widayatno; Abdul Hamid; Didik Prasetyoko (UNIVERSITAS SEBELAS MARET (UNS), 2020)
The present research studied about decolorization of methylene blue dye using photocatalyst ZnO/ZSM-5 under UV-LED lamp. ZnO/ZSM-5 was synthesized using the impregnation method by adding two grams ZSM-5 to Zn solution 0.3 M 10 mL. Photocatalyst was characterized using X-ray diffractometer (XRD), Fourier transform infrared (FTIR), field emission scanning electron microscopy-energy dispersive X-Ray (FESEM-EDX), and surface area analyzer (SAA). Analysis using XRD show addition characteristic peaks of ZnO at 2θ 31.60°, 34.21°, 36.08°, 47.35°, 56.50°, 62.73°, 67.83°, that indicates a successful impregnation process. The photocatalysis activity test was done on methylene blue dye 100 mg L-1. ZSM-5 and ZnO activities were tested under UV-LED irradiation and dark conditions. Data showed that percent removal of dye occurred on ZnO/ZSM-5 under 15 minutes irradiation is 78.32%.